PENGEMBANGAN LMS UNTUK MENDUKUNG MULTIPLE INTELLIGENCES BERBASIS PERSONALISASI - Silalahi, Natalia; Bangun, Melly Br.; Ritonga, Rahmilawati (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2025)
The development of educational technology requires innovation in learning systems that can accommodate the diversity of student characteristics. This study aims to develop and analyze a personalization system in Learning Management Systems (LMS) to support Multiple Intelligences theory for elementary school children through digital integration of Teele Inventory for Multiple Intelligences (TIMI). The research method uses a Design and Development Research (DDR) approach with stages of needs analysis, system design using digital TIMI adaptation, prototype development, internal functionality testing, and expert validation. Research subjects involved 2 validators: experts in educational technology and software engineering. The development results showed that the